Neurology and the military: Five new things - Tsao, Jack W. (Neurol Clin Pract, 2013)
The current Iraq and Afghanistan conflicts have seen the highest survival rates in US service members ever, despite staggering numbers of traumatic brain injury and limb loss cases. The improvement in survival can be attributed at least in part to advances in far-forward, rapid medical treatment, including the administration of hypertonic saline solutions and decompressive craniectomies to manage elevated intracranial pressure. After evacuation to military hospitals in the continental United States, service members who have had limb loss face extensive rehabilitation. The growing amputee population has led to a burgeoning interest in the treatment of phantom limb pain and in the development of advanced prostheses.